Pelatihan Pemetaan Laboratorium Lapangan Terpadu UMGO (LLTUMGO) Dari Foto Udara - Arthur Gani Koto; Suryadi Ilato (Pusat Riset Manajemen dan Publikasi Ilmiah Serta Pengembangan Sumber Daya Manusia Sinergi Cendikia, 2022)
Problems in an area can be quickly handled and managed by providing geospatial information in maps form. The University of Muhammadiyah Gorontalo Integrated Field Laboratory (LLTUMGO) is one field of learning media for the UMGO academic community. As a field of learning of media, a map is needed so in the future, the spatial arrangement and planning can utilize optimally. LLTUMGO was initiated at the beginning of the even semester of 2020-2021. One of the problems that occur is the unavailability of the LLTUMGO map. The map is needed in context structuring and planning the development that will be carried out to make it look attractive. Therefore, an initial step is needed to organize LLTUMGO starting from a map. The objectives of this community service activity are: 1) introduce and train partners in drone operations, 2) introduce area recording techniques, and 3) create LLTUMGO maps. This activity lasts for 1 day. The implementation method used in achieving the above objectives is carried out by providing an explanation and introduction to drones, drone operations, and recording technique practices. The results of this service activity are: 1) partners understand how to operate drones, 2) partners understand area recording techniques, and 3) LLTUMGO maps from aerial photos. In general, it can be concluded that this activity went well of partners were quite enthusiastic in participating in it even though several obstacles occurred in the field. Some of these obstacle include partner disciplines that are not in sync with the material provided and the time is short. Partner disciplines come from study programs with various backgrounds such as agribusiness, animal husbandry, aquaculture, information systems, psychology, and PGSD.